Evaluasi Sistem Maintenance pada Digester Menggunakan Metode FMEA di PT. Perkebunan Nusantara IV Regional II Unit Kebun dan PKS Adolina - Juita Amelia Simanullang; Anitasari Sihotang; Adi Mahendra Pasaribu; Indira Ruth Septarini; Widya Fernanda Putri (Politeknik Kampar, 2025)
This study evaluates the maintenance system of the digester machine at PT Perkebunan Nusantara IV Regional II, Adolina Palm Oil Mill, which plays a crucial role in processing Fresh Fruit Bunches (FFB) into Crude Palm Oil (CPO). The objective of this research is to minimize potential machine failures and downtime while improving the overall efficiency of production operations. To achieve this, the Failure Mode and Effect Analysis (FMEA) method was applied to systematically identify potential failure modes, analyze their causes and effects, and assess their risk levels through the calculation of the Risk Priority Number (RPN). Data collection was conducted using a combination of field observation, in-depth interviews with technicians and operators, and documentation related to equipment performance and historical records of machine failures. The analysis revealed several critical components of the digester with relatively high RPN values, indicating potential risks that require immediate attention. These include issues related to wear and tear of mechanical parts, insufficient lubrication practices, and delays in replacing spare parts. Based on these findings, several corrective and preventive measures were proposed, including the improvement of preventive maintenance schedules, enhancement of operator training programs to increase technical competency, and strengthening of spare parts inventory management to avoid production delays. The study concludes that by addressing the identified failure modes through proactive maintenance strategies, the reliability of the digester machine can be significantly improved. This not only reduces the frequency of breakdowns and maintenance costs but also ensures more stable production performance, thereby supporting the sustainable operation of the palm oil mill